THE USE OF TEACHING PROFICIENCY THROUGH READING AND STORYTELLING (TPRS) IN TEACHING SPEAKING SKILL - Muhammad Anjar Nugraha (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2021)
This study aims at investigating the effectiveness of the Teaching Proficiency through Reading and Storytelling (TPRS) method in teaching speaking skills to the tenth-grade students in one of the senior high schools in Bandung, and their attitudes after the implementation of this method in the classroom. The embedded mixed method design was applied to accomplish the two research questions. The quantitative data were gained from the students speaking pre-test, post-test, and questionnaire. Meanwhile, the qualitative data were taken from classroom observation field notes as the secondary data to capture the treatment process. 24 students in the experimental group and 23 students in the control group were randomly selected as the participant in this study. After seven meetings of the treatment, the data analysis showed that the speaking score of the experimental group that was treated by using language acquisition-based in TPRS was significantly higher than the control group that was treated by using language learning-based in non-TPRS at the .05 level of significance. The null hypothesis of this study was rejected. Since this study had dealt with the low achiever students that most of them were low motivated, TPRS instruction was appropriate to scaffold language in making them comprehensible and accessible. Moreover, the questionnaire data found that the behavioral aspect of students’ attitude on the use of TPRS method in teaching speaking skills was highly positive. TPRS has made the students appreciate more, feel not afraid, avoid anxiety, and have more confidence in speaking English.